(untitled) - Coyne, Mark S. (Clifton Park, NY, 2006)
The book explains the importance of each concept explored, discusses the theory behind each concept, and presents the method for solving each problem. Designed to cover all of the most common equations in the soil science field, from calculating particle size distribution to conducting simple hypothesis testing, this text provides the reader with many opportunities for practice in working out sample problems of each required math concept
Keywords: Soil science,Khoa học đất; Mathematics,toán học